STRATEGY FOR THE IMPLEMENTATION OF THE LAW ON THE PROTECTION OF WOMEN AND CHILDREN IN OVERCOMING SEXUAL VIOLENCE IN CIREBON - Iqbal Maulana Ghozi; Rangga Agin Wijaya; Rio Alexandro; Dea Viqi Alayda Alamsyah; Dadan Taufik Fathurohman (Jurnal Abdisci, 2025)
Abstract. Background. This research was conducted to study the implementation of laws and regulations in handling cases of sexual violence involving children in Cirebon City. Aims. The primary focus of this research is on the work efficiency of the Women and Children Service Unit (PPA) within the Cirebon City Police, as well as Law Number 35 of 2014 and Law Number 12 of 2022, which were implemented. Methods. The research method chosen is qualitative with an empirical juridical approach, which involves data collection through interviews, observations, and document analysis. Result. The research revealed that the Cirebon City Police PPA unit has generally operated in accordance with standard procedures but is still faced with a number of problems, including the limited number of personnel, the low level of legal understanding in the community, and the impact of psychological trauma on victims, which is often a barrier in the investigation process. Conclusion. In addition, the synergy between related institutions, such as the Social Service and child protection institutions, is considered to be unoptimal. Implementation. Therefore, efforts are needed to increase the capacity of law enforcement officials, provide legal education to the public, and strengthen coordination between institutions to increase the effectiveness of legal protection for child victims of sexual violence.